Wild Rubber Extraction in the Peruvian Amazon: local perception and socioeconomic indicators as tools for decision-making - Fitts, Lucia Alejandra; Cruz-Burga, Zoila Aurora; La Torre-Cuadros, María de los Ángeles (Ethnobiology and Conservation, 2020)
Forests play an important role in the life of indigenous communities. However, making nontimber forest management a profitable economic activity is a difficult task. Factors contributing to this difficulty include the increasing pressure from the market economy, which leads communities to opt for alternative economic activities such as agroforestry, timber harvest, cacao, and aquaculture. External institutions have implemented rubber projects to reintroduce the rubber extraction activity, but the outcomes of these projects are unknown. To help address this issue, our research was conducted in the Sinchi Roca I native community in Peru. The objectives were (1) to describe the process of wild rubber (Hevea brasiliensis) extraction; (2) to analyze the local perception by gender of rubber management; and (3) to evaluate the outcomes of this activity using socioeconomic criteria and indicators. Data collection techniques included in-depth interviews, focus group discussions, and intra-household surveys. First, we found that locals once extracted rubber with unsuitable techniques, which have improved with technical forest management. Second, wild extraction has a positive socioeconomic perception for the community, mainly because it provides income for basic needs. Surveyed families extract around 28,800 liters of rubber per year, averaging US 557.80 per family each year. Finally, we found that men and women participate in wild rubber extraction and decision-making. However, women prefer not to actively participate in meetings with external institutions. Despite the benefits found, current use of silviculture techniques and community empowerment should be improved to take better advantage of existing potential.